Research progress of electrical properties based on carbon nanotubes; interconnection. (17th August 2020) - Mei, Huanhuan; Cheng, Yang
Abstract: As an important part of the information revolution, integrated circuits have been developing in a short, light, and high-integration direction in recent years. According to the international semiconductor technology route, copper has encountered bottlenecks in the 22-nm technology node and it is difficult to keep up with the data throughput of processors. The increase of Cu resistivity is aggravated by the problems such as electron scattering, and the mass transfer along interface and grain boundary is one of the most urgent problems to be solved for future technology. Carbon nanotubes are expected to be the next generation of VLSI interconnects due to its large average electron mean free path at micron-scale, high thermal conductivity and current carrying capacity. In this review, we highlight the electrical properties of carbon nanotubes interconnection and interconnection between carbon nanotubes and metal and give a description of the specific processes, advantages and disadvantages of each interconnection technology. The purpose is to provide some useful information and inspiration for future research work of carbon nanotubes interconnection.